The Influence Of Compensation And Work Life Balance On Loyalty Of Gen Z Employees In Tasikmalaya City (Survey Of Gen Z Employees In The Formal Sector): - Melaty, Ajeng Ayu; Sutrisna, Arga; Oktaviani, Nita Fauziah (Universitas Dehasen Bengkulu, 2024)
This research aims to determine the condition of compensation, work life balance and employee loyalty, as well as to test and analyze the influence of compensation and work life balance on the loyalty of Gen Z employees in Tasikmalaya City (survey of Gen Z employees in the formal sector). This type of research uses quantitative causality research and the respondents in this research are 100 respondents. In this research, samples were taken using non-probability sampling, namely using a purposive sampling technique. The analysis was carried out using the multiple linear regression method using IBM SPSS version 26 software. The research results show that compensation and work life balance simultaneously have a significant effect on the loyalty of Gen Z employees in Tasikmalaya City in the formal sector. The results of research on partial compensation on employee loyalty have a significant effect on the loyalty of Gen Z employees in Tasikmalaya City in the formal sector and work life balance partially has a significant effect on the loyalty of Gen Z employees in Tasikmalaya City in the formal sector.